Ảnh hưởng của đoán nghĩa qua ngữ cảnh và sơ đồ ngữ nghĩa đối với khả năng đọc hiểu của người học : - Lý, Bích Tuyền (Trường Đại Học Cần Thơ, 2013)
The current study aims to investigate the effects of guessing meaning from context and semantic mapping on english as a foreign language learner's reading comprehension as well as their attitudes towards the implementation of the two strategies in reading class